Call of Duty: A Case Study of ICT Integration in Philippine Provincial Public Schools in San Isidro Davao Oriental Post K-12 Implementation - Castillo, Lian Sabella (JPAIR Multidisciplinary Research, 2018)
The study delves on the factors and barriers that contribute to the success and failure of ICT integration in Philippine public basic schools. The country is currently undergoing a major reform in its education system, from a K-10 system to a K-12 one encompassing an ICT module. Our case study, San Isidro, Davao Oriental is a partially rural region in the southern island of Mindanao that could be representative of a larger demographic. Exploratory mixed methods design was utilized to answer these questions. An ICT integration self-assessment matrix was constructed on the basis of previous research from UNESCO, The World Bank, OECD, among others. These standards for success were translated into a survey questionnaire distributed among the 21 schools in the municipality. Purposive sampling of schools was pooled for interview and detailed questioning, along with additional field observations. Findings show that human factors such as leadership and teacher motivation are key in realization of these goals. Faculty activity for any such venture, such as ICT integration and innovative pedagogy, is likely limited by the basic infrastructure available within campus grounds. However, as people have the capacity to go above and beyond limitations, it is possible to transcend these limitations and progress towards innovative pedagogy and consequently the next stage in integration.